Methods for broad‐scale plant phenology assessments using citizen scientists’ photographs - Vijay V. Barve; Laura Brenskelle; Daijiang Li; Brian J. Stucky; Narayani V. Barve; Maggie M. Hantak; Bryan S. McLean; Daniel J. Paluh; Jessica A. Oswald; Michael W. Belitz; Ryan A. Folk; Robert P. Guralnick (Applications in Plant Sciences, 2020)
Premise Citizen science platforms for sharing photographed digital vouchers, such as iNaturalist, are a promising source of phenology data, but methods and best practices for use have not been developed. Here we introduce methods using Yucca flowering phenology as a case study, because drivers of Yucca phenology are not well understood despite the need to synchronize flowering with obligate pollinators. There is also evidence of recent anomalous winter flowering events, but with unknown spatiotemporal extents. Methods We collaboratively developed a rigorous, consensus‐based approach for annotating and sharing whole plant and flower presence data from iNaturalist and applied it to Yucca records. We compared spatiotemporal flowering coverage from our annotations with other broad‐scale monitoring networks (e.g., the National Phenology Network) in order to determine the unique value of photograph‐based citizen science resources. Results Annotations from iNaturalist were uniquely able to delineate extents of unusual flowering events in Yucca. These events, which occurred in two different regions of the Desert Southwest, did not appear to disrupt the typical‐period flowering. Discussion Our work demonstrates that best practice approaches to scoring iNaturalist records provide fine‐scale delimitation of phenological events. This approach can be applied to other plant groups to better understand how phenology responds to changing climate.